Violence in the Central Iberian Peninsula during the Bronze Age: A Possible Prehistoric Homicide. (25th May 2012) - JiméNez‐Brobeil, S. A.; Roca, M. G.; Laffranchi, Z.; NáJera, T.; Molina, F.
ABSTRACT One of the most interesting sites of the Bronze Age in the central area of the Iberian Peninsula is La Motilla del Azuer (Daimiel, Ciudad Real), dated between 2200 and 1350 bc. The main objective of this study was to investigate interpersonal violence in this site and to report an uncommon case of violent death. No traumatic injury was detected in any child, and men and women significantly differed in the frequency of traumas. More traumatisms were found in men from the earlier stages of occupation, including a young man with at least three blunt force traumas and 26 sharp force traumas. The archaeological findings and trauma patterns in the skeletons of the 65 individuals studied suggest a relatively intense level of exposure to violence for adult men in the earlier stages of occupation of this settlement. Copyright © 2012 John Wiley & Sons, Ltd.